Teachers' Efficacy in Inclusive Teaching: A Study on EFL Pre-Service Teachers - Damayanti, Agni; Lintangsari, Alies Poetri; Kusumawardani, Irene Nany (The Center for Disability Studies and Services Brawijaya University, 2022)
Examining the perceived efficacy of pre-service teachers in implementing inclusive practices is one approach to see if they are up to the challenge. The instrument of the study was adopted from Prof.Umesh Sharma's article. The old research only does qualitative research. This study aims to check pre-service teachers' efficacy in implementing inclusive education in teaching English. This research used a descriptive quantitative research design to check pre-teacher efficacy to practice inclusive classes in teaching English. The data were collected through a questionnaire with 99 participants from introduction in inclusive education classes. The obtained study shows a positive response toward pre-service teachers' efficacy. The findings show that most participants agree with the statements about the efficacy of using inclusive instructions, collaboration, and management. The more strong the sense of efficacy in the pre-service teacher, the greater the chance for them to succeed in implementing inclusive education in the classroom.